Evaluation of 19 years of international external proficiency testing for high-resolution HLA typing - Voorter, C. E. M.; Groeneveld, L.; Heidt, S.; Wieten, L. (Frontiers in Genetics, 2024)
The international high-resolution external proficiency testing (EPT) started in 2004 with high-resolution typing of human leucocyte antigen (HLA) class I (HLA-A,B,C) and HLA class II (HLA-DRB1, DRB345, DQB1, and DPB1) alleles, since possibilities for such an EPT within Europe were limited and all existing EPTs at that time made use of the comparison of HLA typing results without a reference. This EPT was set up as a collaboration between the HLA laboratory of Leiden, providing DNA samples to the participants, and the laboratory of Maastricht, performing the high-resolution typing as the reference result and evaluating the results of all participants according to the prevailing European Federation for Immunogenetics (EFI) standards. Once a year, 12 samples were sent to the participating laboratories, and evaluation and certificates were provided at the end of that same year. During the years, the EPT was extended to low-resolution HLA class I and II typing, high-resolution typing including DQA1 and DPA1, and allelic resolution typing for HLA class I, the latter one being unique in this field. Evaluation of the high-resolution typing results of the last 19 years showed a clear increase in the number of loci tested by the participating laboratories and a clear change of method from Sanger sequencing with additional other techniques (SSO/SSP) to the nowadays widely used next-generation sequencing method. By strictly using the EFI rules for high-resolution HLA typing, the participants were made aware of the ambiguities within exons 2 and 3 for class I and exon 2 for class II and the presence of null alleles even in a two-field HLA typing. There was an impressive learning curve, resulting in >98% correctly typed samples since 2017 and a 100% fulfillment of EFI rules for all laboratories for all loci submitted in the last 2 years. Overall, this EPT meets the need of an EPT for high-resolution typing for EFI accreditation.